Associations between cigarette smoking status and health-related physical fitness performance in male Taiwanese adults - Ho, Chien-Chang; Lee, Po-Fu; Xu, Shu; Hung, Chang-Tsen; Su, Yan-Jhu; Lin, Chi-Fang; Wu, Min-Chen; Chen, Yun-Tsung (Frontiers in Public Health, 2022)
Background: The highest proportion of smoking behavior occurs in male adults in Taiwan. However, to our knowledge, no study has investigated the relationship between smoking behavior and health-related physical fitness according to education level, health status, betel nut-chewing status and obesity in male adults aged 18 years or older in Taiwan. Aims: This study aimed to determine the associations between cigarette smoking and health-related physical fitness performance in male Taiwanese adults. Methods: This was a cross-sectional study conducted on 27,908 male adults (aged 23-64 years) who participated in Taiwan’s National Physical Fitness Survey 2014-2015. Data from a standardized structured questionnaire, anthropometric variables, and health-related physical fitness measurements were analyzed. Individuals were categorized as never smoking cigarettes, former smoker, and current smoker. Multiple linear regression analysis was performed to evaluate the association between cigarette smoking and health-related physical fitness performance. Results: Never smoking group exhibited a lower (p < 0.05) proportion of abdominal obesity, higher (p < 0.05) proportion of perceived good health status, and greater (p < 0.05) performance in 1-min sit-up and sit-and-reach tests when compared with current smoking and former smoking group. Former smoking group had the highest (p < 0.05) performance in 3-min step test among all groups. Current smoker was significantly negatively (p < 0.05) associated with 3-min step, 1-min sit-up and sit-and-reach tests. Notably, former smoker was significantly positively (p < 0.05) associated with 3-min step and 1-min sit-up tests, but still negatively (p < 0.05) associated with sit-and-reach performance. Conclusion: Current smoker was associated with an increased the risk of abdominal obesity, reduced the perceived health status and health-related physical fitness performance. Quitting smoking had beneficial effect on the perceived good health status, cardiorespiratory and muscular fitness in male Taiwanese adults, but not on flexibility performance. Further research on the ameliorate mechanism underlying this phenomenon is warranted.